Studi Kasus Pada Pasien Diabetes Melitus - Nova, Maria; Yanti, Rahmita (REAL in Nursing Journal, 2020)
Background: According to the International of Diabetic Federation there has been an increase in cases. The incidence of diabetes mellitus according to Riskesdas (2013) data increased from 1.1% in 2007 to 2.1% in 2013 from a total population of 250 million people. This research aims to carry out the process of standard nutritional care in care management clinical nutrition in diabetes millitus patients. Methods: This type of research is descriptive observational and uses purposive sampling method. Results: Patients were diagnosed with diabetes mellitus, the nutritional status of obese patients and the patient's diet was high in energy and fat. Conclusion: Based on the results of monitoring and evaluation on patients and the nutritional status of obese patients, intake before and after the intervention energy deficit is heavy, moderate protein deficit, good fat and carbohydrate deficit is heavy.Keywords: Nutritional Status, Patients, Diabetes Mellitus